Organoleptic Study of Deacidified and Deodourised Palm Oil - Kapil, Umesh; Nayar, Deepika; Sharma, T D (Indian Journal of Community Health, 2014)
Deficiency of vitamin A has long been identified as a serious and preventable nutritional disorder, associated with increased risk of mortality and morbidity amongst children. The present study was conducted with the objectives (i) to perform organoleptic testing of food products cooked in Deacidified and Deodourised Palm oil (DDPO), by sensory evaluation method and (ii) to compare the characteristics of these food products with the same products cooled in routinely used oil. Eleven commonly used weaning food items were prepared with routinely used oil (Group a). The same recipes were also prepared with DDPO (Group B). A food testing panel conducted with sensory evaluation for assessing the acceptability of the various food items. It was observed that with respect to all characteristics there was no significant difference in the recipes made with the two types of oil. Results indicated that DDPO can be used in India for preparation of weaning foods which are routinely given to young children.